Cytochrome P450 monooxygenase genes in the wild silkworm, Bombyx mandarina - Wan,Linrong; Zhou,Anlian; Xiao,Wenfu; Zou,Bangxing; Jiang,Yaming; Xiao,Jinshu; Deng,Cao; Zhang,Youhong; The members of the Genefang Research Team: Zi-yan Huang, Cong-fan Bu, Jie Zeng, Zhao-nan Hao, Yan-peng Chen, and Meng-jia Liu (PeerJ, 2021)
Wild (Bombyx mandarina) and domestic silkworms (B. mori) are good models for investigating insect domestication, as 5000 years of artificial breeding and selection have resulted in significant differences between B. mandarina and B. mori. In this study, we improved the genome assemblies to the chromosome level and updated the protein-coding gene annotations for B. mandarina. Based on this updated genome, we identified 68 cytochrome P450 genes in B. mandarina. The cytochrome P450 repository in B. mandarina is smaller than in B. mori. Certain currently unknown key genes, rather than gene number, are critical for insecticide resistance in B. mandarina, which shows greater resistance to insecticides than B. mori. Based on the physical maps of B. mandarina, we located 66 cytochrome P450s on 18 different chromosomes, and 27 of the cytochrome P450 genes were concentrated into seven clusters. KEGG enrichment analysis of the P450 genes revealed the involvement of cytochrome P450 genes in hormone biosynthesis. Analyses of the silk gland transcriptome identified candidate cytochrome P450 genes (CYP306A) involved in ecdysteroidogenesis and insecticide metabolism in B. mandarina.
Keywords: Bombyx mandarina; Wild silkworm; Cytochrome P450; Gene family